1980
DOI: 10.1111/j.1476-5381.1980.tb10921.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Irritant‐induced Bronchoconstriction in the Spontaneously Breathing Guinea‐pig

Abstract: Inhalation of an aqueous aerosol of citric acid caused bronchoconstriction in anaesthetized guinea‐pigs which was abolished by bilateral vagal section. Conscious guinea‐pigs developed slow, laboured breathing within 90 s of exposure to citric acid aerosol. The onset of this pattern of breathing was delayed by prior aerosol administration of atropine, ipratropium bromide, isoprenaline and tetracaine. The data suggest that exposure of guinea‐pigs to citric acid may be a useful model of reflex bronchoconstriction. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…In earlier studies in guinea-pigs it was found that a large dose of isoprenaline inhibits cough [7,27]. The pre sent data extend the previous results and demonstrate a concentration-related inhibition of both cough and bronchoconstriction by a (T-agonist and two xanthine deriva tives.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In earlier studies in guinea-pigs it was found that a large dose of isoprenaline inhibits cough [7,27]. The pre sent data extend the previous results and demonstrate a concentration-related inhibition of both cough and bronchoconstriction by a (T-agonist and two xanthine deriva tives.…”
Section: Discussionsupporting
confidence: 79%
“…This study confirmed that the bron choconstriction induced by citric acid in guinea-pigs in volves a muscarinic mechanism [6,7]. Citric acid-induced bronchoconstriction is also attenuated by atropine in man [8].…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, airway contractility affects the frequency of cough induction. It is known that citric acid induced cough is produced by effects on bronchoconstriction involving with the muscarinic mechanism [2,7]. Vagal blocking by atropine aerosols significantly decreased the number of coughs in both BHS and BHR.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a larger contribution of airway C-fibers on the airway contraction was observed in BHS compared with BHR in a preliminary experiment. It is known that citric acid-induced cough is produced by the effect of citric acid on capsaicin-sensitive sensory neurons [6,7], while the bronchoconstriction induced by citric acid in guinea pigs involves a muscarinic mechanism [2,6]. It is, therefore, interesting to investigate the relationship between cough occurrence and airway sensitivity in these model animals with different muscarinic functions and the role of C-fibers in the airway.…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation of an aqueous solution of citric acid is known to cause airway chemoreceptor irritation in man and in guinea-pig, and this response appears to involve sensory mechanisms linked to the cough re¯ex (Kase 1968;Turner 1968). It has been demonstrated that citric acid-induced cough by stimulating sensitive sensory nerves and bronchoconstriction induced by citric acid in guinea-pigs involves a muscarinic mechanism (Allott et al 1980;Forsberg & Karlsson 1986;Forsberg et al 1988).…”
Section: Discussionmentioning
confidence: 99%